Falx and interhemispheric fissure on axial CT: II. Recognition and differentiation of interhemispheric subarachnoid and subdural hemorrhage. - Zimmerman, R D; Russell, E J; Yurberg, E; Leeds, N E (American Journal of Neuroradiology, 1982)
Interhemispheric hyperdensity or unenhanced computed tomography was originally considered a sign of subarachnoid hemorrhage, the "falx sign." It has since been identified as a normal feature and has also been seen with interhemispheric subdural hemorrhage. To determine the differential features of interhemispheric hemorrhage, 50 patients with subarachnoid hemorrhage and 32 patients with interhemispheric subdural hematomas were reviewed. Subarachnoid hemorrhage produced anterior interhemispheric hyperdensity only, with a zigzag contour and extension from the calvarium to the rostrum of the corpus callosum. Interhemispheric subdural hematomas produce unilateral crescentic hyperdensities that are largest in the posterior superior part of the fissure, behind and above the splenium of the corpus callosum. Interhemispheric hyperdensity in children is more complex. Because the anterior part of the fissure is narrow in younger patients, subarachnoid hemorrhage may go undetected. Likewise, interhemispheric subdural hematomas in children are smaller and more difficult to recognize. They produce asymmetric thickening of the falx shadow with extension over the tentorium. They are, however, of great significance since they are generally seen in abused patients and carry a poor prognosis.